Knowledge comes but wisdom lingers! Learning orientation as the decisive factor for translating social capital into organisational innovativeness and performance in Turkey - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2019)
The Turkish economy has been growing fast and Turkish organisations increasingly rival their Western competitors in terms of innovativeness. While strategy scholars primarily focus on internal capabilities such as learning orientation, network scholars typically consider external network ties as determinants of organisational success. Building on both research streams, our study develops and empirically tests an integrative framework that incorporates the specific cultural context of Turkey. Based on empirical data from 178 organisations, we demonstrate that in Turkey organisational innovativeness results from learning orientation mediating the effect of network ties on innovativeness. Thus, our study links external and internal explanations of what drives innovativeness and suggests that organisations in Turkey need to develop a network-enabled orientation towards learning. We make important recommendations for managers of Turkish organisations and those wishing to enter the Turkish market.
Keywords: learning orientation; network ties; innovativeness; performance; emerging economies; Turkey; RESEARCH-AND-DEVELOPMENT; PRODUCT DEVELOPMENT; ENTREPRENEURIAL ORIENTATION; ABSORPTIVE-CAPACITY; MARKET ORIENTATION; INDIVIDUALISM-COLLECTIVISM; RELATIONAL EMBEDDEDNESS; TECHNOLOGY VENTURES; NATIONAL CULTURE; FIRM PERFORMANCE